2020
DOI: 10.1155/2020/2489175
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Transcriptomic and Proteomic Analysis Identifies Significant Novel Pathways for Henoch‐Schönlein Purpura Nephritis Progression

Abstract: Background. Although Henoch-Schönlein purpura nephritis (HSPN) is characterized by glomerular deposition of aberrantly glycosylated immunoglobulin A1 (IgA1), the underlying mechanism of HSPN progression has not yet been completely elucidated. In this study, we integrated transcriptomic and proteomic analyses to explore the underlying mechanism of HSPN progression. Methods. RNA sequencing and tandem mass tag- (TMT-) based quantitative proteomics were used to gain serum transcriptomic and proteomic profiles of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…By integrative analysis of transcriptomics and proteomics, Xie et al. identified a cluster of serums mRNAs and proteins and four pathways including JAK-STAT, mTOR, SWI/SNF and Wnt closely related to IgAVN progression ( 4 ). By bioinformatic study of proteins identified by iTRAQ, Gao et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By integrative analysis of transcriptomics and proteomics, Xie et al. identified a cluster of serums mRNAs and proteins and four pathways including JAK-STAT, mTOR, SWI/SNF and Wnt closely related to IgAVN progression ( 4 ). By bioinformatic study of proteins identified by iTRAQ, Gao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, rapidly evolving bioinformatic and functional analysis play an important role to define the fundamental mechanisms of disease pathogenesis. By integrative analysis of transcriptomics and proteomics, Xie et al identified a cluster of serums mRNAs and proteins and four pathways including JAK-STAT, mTOR, SWI/SNF and Wnt closely related to IgAVN progression (4). By bioinformatic study of proteins identified by iTRAQ, Gao et al revealed that differential genes were mainly enriched in lipid metabolism and adhesion connection pathways, among which CDC42 and CTNNB1 were potential candidates involved in the pathogenesis of IgAVN (5).…”
Section: Introductionmentioning
confidence: 99%
“…Since differential gene expression plays an important role in the onset and progression of the disease, at the level of mRNA and protein, a combined approach is needed to better understand the mechanism of onset of the disease, with integration of different "omics" techniques, including proteomics and transcriptomics [28]. Thanks to the use of proteomics, especially targeted proteomics, promising biomarkers can be identified, which can help stratify patients with respect to the risk of developing kidney disease progression and may contribute to the earlier diagnosis of kidney disease [29,30].…”
Section: Generalizability and Future Applicationmentioning
confidence: 99%
“…Thanks to the use of proteomics, especially targeted proteomics, promising biomarkers can be identified, which can help stratify patients with respect to the risk of developing kidney disease progression and may contribute to the earlier diagnosis of kidney disease [29,30]. The combined approach, in terms of the integration of transcriptomics and proteomics, reveals new molecular pathways and mechanisms of kidney disease progression in IgAV, which represent potential clues for the development of new therapeutic approaches [28].…”
Section: Generalizability and Future Applicationmentioning
confidence: 99%
“…"Omics" has been widely used in exploring the underlying mechanisms of disease development. Recent reports have investigated omics in IgA vasculitis [6][7][8][9]. We published a metabolomic study that revealed potential biomarkers associated with the progression of IgAV to IgAV with nephritis [10].…”
Section: Introductionmentioning
confidence: 99%